FORMATION OF CHILD CHARACTER THROUGH RELIGIOUS CULTURE - Miftahul Jannah; Husin; Wafiq Azizah; Rizka Maulida; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Religious values ​​are very important values ​​in education, especially for strengthening the character of early childhood. Therefore, children are taught about character education so they can behave well. It is very important to shape the character of children through habituation methods in the family, school and environment. with this habituation, the character will grow and develop positively according to Islamic teachings. This study aims to describe the importance of religious values ​​in the formation of children's character, its implementation and influence in everyday life, through religious habits such as praying in congregation, and as etiquette with peers, teachers, as well as parents. This study uses a descriptive qualitative approach obtained from interviews with teachers and madrasa heads, The research results obtained are the importance of instilling religious values ​​in early childhood, related to the religious culture that is applied is the habit of praying Dhuha in congregation, morning Quran, following the commemoration of Islamic holidays. Whereas regarding Islamic character education through religious habituation is to apply religious habituation which is carried out every day as a process of forming children's character to behave noble, obedient to worship, honest, tolerant, care for the environment, responsible and become the foundation of faith for children, good character will emerge if religious values ​​are getting stronger and more instilled in the child's environment, both in the family environment and the school environment.